Effects of malic or citric acid on the fermentation quality, proteolysis and lipolysis of alfalfa silage ensiled at two dry matter contents. Issue 5 (14th September 2021) - Ke, Wencan; Ding, Zitong; Li, Fuhou; Xu, Dongmei; Bai, Jie; Muhammad, Ishaq; Zhang, Yixin; Zhao, Liansheng; Guo, Xusheng
Abstract: This study evaluated the effects of two organic acids on the fermentation of alfalfa silages at different dry matter (DM) contents. Alfalfa was wilted to DM contents of 30% (moderately low) and 38% (normal) and ensiled without additives (control) or treated with 0.6% fresh matter DL‐malic acid (MA) or 0.6% fresh matter citric acid (CA) for 60 days. After ensiling, silages with a normal DM were higher in pH, water‐soluble carbohydrates (WSC) and DM loss ( p  < 0.05) when compared to silages ensiled at a moderately low DM. The higher DM content also limited proteolysis in silages indicated by lower concentrations of ammonia N (NH3 ‐N). Compared with the control group, MA and CA‐treated silages had lower pH, lower concentrations of acetic acid and NH3 ‐N but higher concentrations of lactic acid. The addition of MA and CA reduced DM losses in silages when compared to the control group except for MA‐treated silage at a moderately low DM in which only numerically lower DM loss was observed. Malic acid and CA also resulted in a higher proportion of polyunsaturated fatty acids, especially in silages with a moderately low DM. Including MA and CA could promote silage fermentation, limit proteolysis and lipolysis at the lower and medium‐to‐high end of DM contents in alfalfa silages.